Identifying magnetic reconnection events using the FOTE method. Issue 2 (12th February 2016) - Fu, H. S.; Cao, J. B.; Vaivads, A.; Khotyaintsev, Y. V.; Andre, M.; Dunlop, M.; Liu, W. L.; Lu, H. Y.; Huang, S. Y.; Ma, Y. D.; Eriksson, E.
Abstract: A magnetic reconnection event detected by Cluster is analyzed using three methods: Single‐spacecraft Inference based on Flow‐reversal Sequence (SIFS), Multispacecraft Inference based on Timing a Structure (MITS), and the First‐Order Taylor Expansion (FOTE). Using the SIFS method, we find that the reconnection structure is an X line; while using the MITS and FOTE methods, we find it is a magnetic island (O line). We compare the efficiency and accuracy of these three methods and find that the most efficient and accurate approach to identify a reconnection event is FOTE. In both the guide and nonguide field reconnection regimes, the FOTE method is equally applicable. This study for the first time demonstrates the capability of FOTE in identifying magnetic reconnection events; it would be useful to the forthcoming Magnetospheric Multiscale (MMS) mission. Key Points: FOTE is the most efficient and accurate method to identify reconnection FOTE can be used in both the guide and nonguide field reconnection FOTE is useful to the MMS mission